Balancing changing values and needs - Moore, Bruce C., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 1998)
The needs of the West have changed dramatically since the beginning of the century. Demands on Western water continue to grow rapidly, while changing societal values and greater environmental knowledge and awareness have demonstrated the need for Reclamation projects to be operated in a more environmentally beneficial manner. Today, residential, industrial, agricultural, recreational, hydropower, and environmental needs all compete for this finite resource. These changing needs have increased Reclamation's responsibilities and resulted in a fundamental shift and evolution in Reclamation's mission. With concern growing over the negative impacts affecting the Glen and Grand Canyons, in 1982 the Secretary of the Interior (Secretary) initiated the two-phase, multi-agency Glen Canyon Environmental Studies (GCES) to better understand the environmental and recreational impacts associated with the operations of the dam. Findings from these studies led to a July 1989 decision by the Secretary for Reclamation to prepare an environmental impact statement (EIS) to reevaluate dam operations in order to determine specific options that could be implemented to minimize, consistent with law, adverse impacts on the downstream environment and cultural resources, as well as Native American interests in the canyons. One of the key elements outlined in the Glen Canyon Environmental Impact Statement (GCEIS) and mandated by the Record of Decision (ROD) is an "Adaptive Management Program" (AMP). The AMP is intended to provide the organization with a process to ensure that scientific information and recommendations from a diverse group of stakeholders are incorporated into the evaluation, management, and future decisions of Glen Canyon Dam operations. The AMP calls for the continued interaction of managers and scientists to monitor the effects of current dam operations on the Colorado River ecosystem, and to conduct research on alternative dam operating criteria that may be necessary to ensure continued protection of resources and improve natural processes. As the 21st century comes into focus, Reclamation is prepared to meet the continuing challenge of bringing together competing interests to find consensus-based solutions to contemporary Western water management challenges. The paper will describe the sequence of events leading up to an EIS on Glen Canyon Dam operations, the implementation of the AMP, and a special event, the Beach Habitat Building Flow.
USCID conference on shared rivers
Not digitized by CSUL Digital Services.
Presented at River basin management to meet competing needs: proceedings from the USCID conference on shared rivers held on October 21-31, 1998 in Park City, Utah.